2022
DOI: 10.22266/ijies2022.0831.12
|View full text |Cite
|
Sign up to set email alerts
|

Secure Cluster based Routing Using Improved Moth Flame Optimization for Wireless Sensor Networks

Abstract: Wireless Sensor Network (WSN) is developed as a promising technology for a wide range of applications due to its low installation cost. However, the nodes in the WSN are susceptible to different security threats, because these nodes are located in hostile or harsh environments. The important goal of this paper is to obtain secure data transmission while minimizing energy consumption. In this paper, an Improved Moth Flame Optimization (IMFO) is used for selecting the optimal Cluster Head (CH) from the network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The performance of the M-TCRSA method is analyzed using packet delivery ratio (PDR), throughput, end to end delay (EED), jitter and life expectancy. The existing methods such as TAGA [17], TCELR [20], SCRIMFO [21] and CCCSA [22] are used to evaluate the performance of M-TCRSA method where these existing methods are developed for the same specifications mentioned in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The performance of the M-TCRSA method is analyzed using packet delivery ratio (PDR), throughput, end to end delay (EED), jitter and life expectancy. The existing methods such as TAGA [17], TCELR [20], SCRIMFO [21] and CCCSA [22] are used to evaluate the performance of M-TCRSA method where these existing methods are developed for the same specifications mentioned in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…From Fig. 3, it is concluded that the M-TCRSA achieves higher throughput than the TAGA [17], TCELR [20], SCRIMFO [21] and CCCSA [22]. The higher throughput is achieved in M-TCRSA because of avoiding malicious attacks and node failure using trust and energy fitness metrics.…”
Section: Throughputmentioning
confidence: 94%
See 3 more Smart Citations